The Formation of Risk Sharing Networks. - Fafchamps, M; Gubert, F (2007)
This paper examines the formation of risk sharing networks in the rural Philippines. We find that geographic proximity--possibly correlated with kinship--is a major determinant of mutual insurance links among villagers. Age and wealth differences also play an important role. In contrast, income correlation and differences in occupation are not determinants of network links. Reported network links have a strong effect on subsequent gifts and loans. Gifts between network partners are found to respond to shocks and to differences in health status. From this we conclude that intra-village mutual insurance links are largely determined by social and geographical proximity and are only weakly the result of purposeful diversification of income risk. The paper also makes a methodological contribution to the estimation of dyadic models.